PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA KANTOR IMIGRASI PAREPARE - Berna, Berna (DECISION : Jurnal Ekonomi dan Bisnis, 2022)
The Immigration Office class II TPI Parepare City is one of the technical implementation units of immigration within the ranks of the Ministry of Law and Human Rights which is directly responsible to the Office of the Ministry of Law and Human Rights in Parepare. The phenomenon shows that the efforts to improve employee performance at the Parepare Immigration Office are less than optimal, one of which is that employees are usually not included in education and training related to their duties and functions. This study aims to determine the effect of work environment and work discipline on employee performance at the Parepare Immigration Office. The data collection techniques used in this study were questionnaires, observations, and literature studies. The sample in this study amounted to 46 respondents. Technical analysis of data in this study using multiple linear analysis techniques. The results of this study partially Work Environment (XI) has a positive and significant effect on Employee Performance (Y). Partially, Work Discipline (X2) has a positive and insignificant effect on Employee Performance (Y). Simultaneously the Work Environment (XI), Work Discipline (X2) have a positive and significant effect on Employee Performance (Y).